Ectomycorrhizal morphology and soil nutrient status control the C: N: P: K stoichiometry in Faxon fir (Abies fargesii var. faxoniana), in the subalpine forests of Southwest China - Chen, Lulu; Li, Xuhua; Tang, Zuoxin (Frontiers in Plant Science, 2025)
The stoichiometry of plant carbon (C), nitrogen (N), phosphorus (P), and potassium (K) provides insights into the nutritional and growth strategies of trees in changing environments. However, abiotic and biotic effects on nutrient stoichiometry in trees of subalpine forests, in the context of climate change, are not fully understood. We focused on the dominant tree species, Faxon fir (Abies fargesii var. faxoniana) located on the eastern edge of the Tibetan Plateau to examine the dynamics and balance of C, N, P, and K in plant tissues, and their driving factors across different habitats. As this tree is typically associated with ectomycorrhizal fungi, we compiled a new dataset of ectomycorrhizal functional traits to evaluate their importance in tree-nutrient stoichiometry. We found that K was the most limiting nutrient in the roots (1.1 ± 0.08 mg g-1) and foliage (10.8 ± 0.3 mg g-1) in Faxon fir and probably the main factor for productivity constraints. Faxon fir exhibited preferential allocation of N, P, and K nutrients to leaves in contrast to roots. Variations in C:N:P:K stoichiometry were primarily explained by soil variables, followed by ectomycorrhizal traits. Specifically, foliar nutrient stoichiometry was closely associated with the formation and morphological traits of ectomycorrhizal root tips, whereas root nutrient stoichiometry was related to the one- (length) and two- (area) dimensional foraging spaces radiated by the ectomycorrhizal mycelium. Our findings demonstrate an imbalance in C:N:P:K stoichiometry in Faxon fir within the changing environments of subalpine ecosystems and highlight the crucial regulatory role of ectomycorrhizal functional traits in mediating these imbalances.